The orphan receptor TR3 participates in angiotensin II‐induced cardiac hypertrophy by controlling mTOR signalling. Issue 1 (29th November 2012) - Wang, Rong‐Hao; He, Jian‐Ping; Su, Mao‐Long; Luo, Jie; Xu, Ming; Du, Xiao‐Dan; Chen, Hang‐Zi; Wang, Wei‐Jia; Wang, Yuan; Zhang, Nan; Zhao, Bi‐Xing; Zhao, Wen‐Xiu; et al.
Abstract: Angiotensin II (AngII) induces cardiac hypertrophy and increases the expression of TR3. To determine whether TR3 is involved in the regulation of the pathological cardiac hypertrophy induced by AngII, we established mouse and rat hypertrophy models using chronic AngII administration. Our results reveal that a deficiency of TR3 in mice or the knockdown of TR3 in the left ventricle of rats attenuated AngII‐induced cardiac hypertrophy compared with the respective controls. A mechanistic analysis demonstrates that the TR3‐mediated activation of mTORC1 is associated with AngII‐induced cardiac hypertrophy. TR3 was shown to form a trimer with the TSC1/TSC2 complex that specifically promoted TSC2 degradation via a proteasome/ubiquitination pathway. As a result, mTORC1, but not mTORC2, was activated; this was accompanied by increased protein synthesis, enhanced production of reactive oxygen species and enlarged cell size, thereby resulting in cardiac hypertrophy. This study demonstrates that TR3 positively regulates cardiac hypertrophy by influencing the effect of AngII on the mTOR pathway. The elimination or reduction of TR3 may reduce cardiac hypertrophy; therefore, TR3 is a potential target for clinical therapy. Abstract : Persistent cardiac hypertrophy ultimately leads to cardiovascular disease. Here, the authors show that the nuclear receptor TR3 participates in angiotensin‐induced cardiac hypertrophy by controlling mTORC1 signaling.